Career development and individuals with physical disabilities. Issue 2 (6th May 2014) - Villanueva-Flores, Mercedes; Valle-Cabrera, Ramón; Bornay-Barrachina, Mar
Abstract : Purpose: – Few studies have focussed on the situation of employees with physical disabilities from the perspective of human resources management – in particular on the career development expectations of this group. The purpose of this paper is to meet this need by focussing on individuals with physical disabilities in Andalusia (Spain). It analyzes three key aspects: whether the perception of discrimination is related to the perception of inequity due to their disabilities, with this relationship being moderated by gender; whether these perceptions of inequality and discrimination lead to feelings of dissatisfaction with the employing organization; and whether the perception of discrimination mediates the relationship between perceived inequity and job dissatisfaction. Design/methodology/approach: – Using the theoretical framework of organizational justice, regression analysis is applied to test the hypotheses in a population of 459 employed people with physical disabilities. Findings: – The results show that perceived discrimination is due to perceived inequity when peers who do not have a disability are used as comparative reference; however, this relationship is not moderated by gender. These perceptions of inequity and discrimination cause individuals to feel dissatisfaction in organizations, and a mediating effect is found for the perception of discrimination in professional development opportunities. The control variables considered, age and education, are not significant in the relationships studied. Originality/value: – An original and valued model is proposed to explain job dissatisfaction among employees with physical disabilities and the possibility of perceiving a dual disadvantage, in their possibilities for professional development. The model links together three variables that have not previously been linked all together in the literature – perceived inequity, perceived discrimination on the grounds of disability, and dissatisfaction – highlighting that perceived discrimination on the grounds of disability mediates the relationship between perceived inequity and dissatisfaction. This model can also examine whether a dual disadvantage is perceived owing to an individual's being a woman and having a disability, considering gender as a variable that moderates the relationship between perceived inequity and perceived discrimination on the grounds of disability.